Tunable microcellular and nanocellular morphologies of poly(vinylidene) fluoride foams via crystal polymorphism control. Issue 1 (5th November 2018) - Leung, Siu N.; Lee, Ji E.
Abstract : Poly(vinylidene) fluoride (PVDF) is well‐known for its polymorphism. Among its different polymorphs, both α and β phase crystals have melting temperatures ranging from 167°C to 172°C. The melting temperature of γ phase crystal, depending on its origin, is about 8 °C or 18°C higher than those of α and β phase crystals. Herein, this article reports a novel approach to tune the microcellular and nanocellular structures of PVDF foams by controlling the polymorphism of PVDF before it is subjected to supercritical carbon dioxide foaming. It has been revealed that altering PVDF's polymorphs can selectively fabricate PVDF foams that possess either (1) closed cells or open cells; (2) unimodal cells or bimodal cells; and (3) microcellular structures or nanocellcular structures. This represents an innovative processing route to fine‐tune the morphologies of PVDF foams, and thereby to tailor their multifunctional properties. Abstract : Poly(vinylidene) fluoride (PVDF) is well‐known for its polymorphism. Herein, this article reports a novel approach to tune PVDF foam structures by controlling the polymorphism of PVDF before it is subjected to supercritical carbon dioxide foaming. It has been revealed that altering PVDF's polymorphs can selectively fabricate PVDF foams with versatile morphologies, and thereby tailor their multifunctional properties.